Effects of Shock and Vibration on Product Quality during Last-Mile Transportation of Ebola Vaccine under Refrigerated Conditions - Linda Bus-Jacobs; Rute Lau; Marjolein Soethoudt; Lisa Gebbia; Edwin Janssens; Tjeerd Hermans (Emerging Infectious Diseases, 2024)
Analyzing vaccine stability under different storage and transportation conditions is critical to ensure that effectiveness and safety are not affected by distribution. In a simulation of the last mile in the supply chain, we found that shock and vibration had no effect on Ad26.ZEBOV/MVA-BN-Filo Ebola vaccine regimen quality under refrigerated conditions.